Meta-Analysis: Effects of Adolescent's Knowledge, Attitude, and Parental Support, on Human Papilloma Virus Immunization Uptake - Wiwit Marliana; Uki Retno Budihastuti; Eti Poncorini Pamungkasari (Journal of Health Promotion and Behavior, 2023)
Background: Human papillomavirus (HPV) is one of the most common sexually transmitted viruses worldwide. HPV vaccination coverage is still low, especially for adolescents, some influential factors are lack of knowledge, rejection, and support of the closest environment in receiving vaccination services. This study aims to estimate the effect size of knowledge, attitudes, and parental support on the use of HPV immunization services in adolescents. Subjects and Method: A systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on eligibility criteria with the PICO Model. Population: female adolescents, Intervention: high knowledge, positive attitude, strong parental support, Comparison: less knowledge, negative attitude, poor parental support, Outcome: Use of HPV immunization services. The articles used were from Google Scholar, Europe PMC, PubMed, and Science Direct published from 2016 – 2023. The keywords used in the search were “adolescent" OR "young women" OR "Parental of Adolescent” AND "Knowledge" AND "attitude" OR "awareness" AND "HPV" OR "HPV Vaccination" OR "Immunization". The study subjects were female adolescents, and articles published in English. The study used multivariate analysis with an adjusted Odds Ratio. Eligible articles were analyzed using the RevMan 5.3. Results: The meta-analysis included 10 cross-sectional studies from Asia, Australia, Africa, Europe, and America. High knowledge increased the likelihood of HPV immunization uptake in female adolescents (aOR= 3.24; 95% CI = 2.43 to 4.32; p<0.001). The meta-analysis included 7 cross-sectional studies showed that positive attitude increased HPV immunization uptake in female adolescents (aOR= 4.10; CI 95% = 2.78 to 6.05; p<0.001). 7 cross-sectional studies showed that strong parental support increased HPV immunization uptake (aOR=2.53; CI95% = 1.79 to 3.58; p< 0.001). Conclusion: High knowledge, positive attitude, and strong parental support increase the likelihood of HPV immunization uptake. Keywords: knowledge, attitude, parental support, adolescents, HPV vaccination. Correspondence: Wiwit Marliana. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: marlianwi.midwifery@gmail.com. Mobile: +6282118277592.